Tectono-stratigraphic Evolution of the Simeulue Forearc Basin, NW Sumatra - Edyta Frankowicz (Berita Sedimentologi, 2011)
This paper presents a tectono-stratigraphic evolutionary model for the Simeulue forearc basin. The Simeulue basin is located offshore NW Sumatra and it is bounded to the west by Simeulue Island and the dextral strike-slip (transpressive) Mentawai Fault System. The basin extends over 260 km in NW-SE direction and 100 km in SW-NE direction. It consists of a deep water area with maximum water depth of approx. 1300 m and contains up to 6 sec TWT of Neogene sediments, most of which are siliciclastics expected to have been derived from Sumatra mainland. The Miocene carbonate build-ups have been the main hydrocarbon exploration target in the basin.